Purun and The Bitter Realities of Women’s Struggle in Peatland Areas - Taqiyuddin Ibnu Syihab; Yustina Ambirini Murdiningrum; Lukas Rumboko Wibowo (Jurnal Perempuan, 2020)
This paper aims to examine the elimination process of traditional conservation that has been built for many years by women on peatlands. This article reveals the struggle and multiple burdens of women in conservation, to do reproductive and productive work in the midst of clashing interests in peatland area. Research conducted shows that there is a shift in the mode of production from subsistence toward exploitative hegemony by capitalistic interests, as a product of modern scientific knowledge. Corporations compete for peatland areas to accumulate endless capital which then threatens the purun and the purun weaving community of women. This has not only led to degradation of the purun ecosystem but also the loss of source of life and cultural identity for the purun weaving community. From an ecofeminist perspective, investment policies and regimes with minimum controls have systematically destroyed peat ecosystems, resulting in economic powerlessness and impoverishment of women.